Notes on Coptic Possessive Predication - Speransky, Nina (Zeitschrift für ägyptische Sprache und Altertumskunde, 2020)
The aim of this paper is to present a linguistically valid description of Coptic (or, more precisely, Sahidic) possessive predication construction, both from the diachronic and the synchronic points of view. The first section treats the complex possessive predication system in Demotic, largely based upon Quack 2020 with some additional observations. The second section discusses possible causes for the shift of the possessor-argument, introduced by the preposition mtw -, to the immediate proximity of the existential verboid wn -. Section 3 aims to explain the origin and the usage of the double suffix possessive pattern (ⲉⲧⲉⲟⲩⲛⲧⲁ-ⲓ-ϥ). Section 4 deals with argument marking in the Sahidic possessive predication, looking for the features that speak for or against the ‘have-drift’. Section 5 discusses the syntactic alternatives of the ⲟⲩⲛⲧⲁ-pattern. The final section attempts to find the semantic mechanisms behind the use of the adverb ⲙⲙⲁⲩ in the basic possessive predication pattern.